World report on disability 2011 (WHO GenevaCH, 2011)
Focuses on measures to improve accessibility and equality of opportunity; promoting participation and inclusion; increasing respect for the autonomy and dignity of persons with disabilities. Defines disability, introduces the International Classification of Functioning, Disability and Health (ICF). Includes recommendations to provide broad policy and practice considerations.
Keywords: DISABILITY